(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The aim of the research is to identify the attitudes of secondary school teachers towards the use of the inverted learning strategy in teaching science, and to study differences in their attitudes according to gender variables, years of teaching experience, scientific qualification and computer literacy. The research was based on a descriptive method. A questionnaire was designed and distributed to a random sample of (200) teachers and schools, (187) of which were fully valid and valid for statistical analysis, with a response rate of (93.5%). The research found a number of results, the most important of which is that the attitudes of secondary school teachers towards the use of the inverted learning strategy in teaching science is positive and relatively important (79.9%). Where they have a desire to use this strategy because of their positive implications for the educational process from their point of view, where teachers emphasize that inverted learning contributes to increasing learning time by transforming the process of home learning and solving homework in the classroom, and provides a stimulating learning environment Share learners in the responsibility of learning. The results showed no statistically significant differences between the average scores of teachers in secondary education in Lattakia in their attitudes towards the use of the inverted learning strategy according to the gender variable, while there were statistically significant differences according to the variables of the academic qualification and the years of teaching experience and computer knowledge.